Characteristics of Undergraduate Students with Disabilities: Disability Disclosure and Academic Persistence - Thompson-Ebanks, Valerie; Jarman, Michelle (Advances in Social Sciences Research Journal, 2017)
This pilot study used a 14-question online survey to examine two key characteristics of undergraduate students with self-identified disabilities: nondisclosure/disclosure to disability services; and utilization of accommodations through disability support services. A total of 10,100 students were sent the survey and 111 were returned completed. Of the 111 completed surveys, 31 students identified as having disabilities perceived to interfere with academic performance. The most notable difference between the characteristics of students with disabilities who disclosed to disability services and those who did not disclose was the prevalence of nondisclosure among students with self-identified psychological disabilities. Recommendations for university and college administrators are included. Key words: students with disabilities; undergraduates; college/university; disability disclosure; disability support services.